Effect of Brand Awareness, Brand Image and Brand Loyalty on Purchase Decicion - Rara Ririn Budi Utaminingtyas; Luqman - Khakim; Anugraha Hadi S (JOBS (Jurnal Of Business Studies), 2023)
The event organizer business is currently very developed its very much need, such as the CV Berkah Jaya event organizer in Purwokerto, there are many competitors. Branding strategy.The activities of collecting, processing, analyzing and presenting data this time are intended analyze the effect of Brand Awareness, Brand Image and Brand Loyalty in order to make Purchasing Decisions at the CV Berkah Jaya Bejo Production - Purwokerto event organizer using sampling with saturated sampling technique of 30 responders. This study used a questionnaire for data collection methods. This research uses quantitative with the analysis method of validity test, reliability test, multiple linear regression analysis, simultaneous test (f test), coefficient of determination (R2) and partial test (t test). This study uses spss which results in the equation Y = -2.116 + 0.483 (X1) + 0.468 (X2) + 0.317 (X3) + e along with the results of R2 0.594 or 59.4% and the rest is a variable that is not studied. The conclusion obtained is that the influence of Brand Awareness, Brand Image and Brand Loyalty for Decision Making has a significant positive effect.